2016
DOI: 10.1103/physics.9.3
|View full text |Cite
|
Sign up to set email alerts
|

A One-Sided View of Acoustic Traps

Abstract: We demonstrate the trapping of elastic particles by the large gradient force of a single acoustical beam in three dimensions. Acoustical tweezers can push, pull and accurately control both the position and the forces exerted on a unique particle. Forces in excess of 1 micronewton were exerted on polystyrene beads in the submillimeter range. A beam intensity less than 50 W=cm 2 was required, ensuring damage-free trapping conditions. The large spectrum of frequencies covered by coherent ultrasonic sources provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…For the case of small objects satisfying the Rayleigh limit, the objects are subjected to either a streaminginduced drag force or the acoustic radiation forces due to the gradients of force fields in the liquid or a combination of both. 30 The manipulation of large droplets considered in the present study falls in the Mie-scattering regime, 25 where the objects experience significantly larger radiation forces due to the multiple reflection and transmission of waves within the droplets, distinct from small object manipulation. Moreover, the droplet trapping method demonstrated in this study is driven by traveling SAWs generated from a single interdigitated electrode (IDT) and hence is different from conventional trapping methods such as acoustic tweezers that utilize standing acoustic wave fields.…”
Section: ■ Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…For the case of small objects satisfying the Rayleigh limit, the objects are subjected to either a streaminginduced drag force or the acoustic radiation forces due to the gradients of force fields in the liquid or a combination of both. 30 The manipulation of large droplets considered in the present study falls in the Mie-scattering regime, 25 where the objects experience significantly larger radiation forces due to the multiple reflection and transmission of waves within the droplets, distinct from small object manipulation. Moreover, the droplet trapping method demonstrated in this study is driven by traveling SAWs generated from a single interdigitated electrode (IDT) and hence is different from conventional trapping methods such as acoustic tweezers that utilize standing acoustic wave fields.…”
Section: ■ Introductionmentioning
confidence: 96%
“…31−34 Single-source trapping methods are fundamentally different and offer greater flexibility compared to multiple-source trapping techniques as the former can trap particles or cells using traveling waves from only one side. 30 We first present the experimental details, including the design of the microwell and the working principle. Then, we experimentally demonstrate the trapping phenomenon for a single aqueous droplet and characterize the trapping phenomenon in terms of the operating power for different droplet sizes and densities.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary analytical studies show that the feasibility of acoustic tweezers and trapping an arbitrarily located object mainly comes from the focused Gaussian ultrasound beam (Azarpeyvand and Azarpeyvand, ; Lee et al, ; Lee and Shung, ; Mitri, ; Wu and Du, ). These studies have shown that Gaussian beams can be used for trapping particles in both lateral and axial directions, although the latter is much harder due to the existence of the radiation force from scattering by pushing the particle away from the transducer (Hill, ; Marzo et al, ). To overcome this problem, single Bessel vortex beam was introduced into the study of SBAT, which can produce a negative axial radiation force (Mitri, , ,, ).…”
Section: Introductionmentioning
confidence: 99%
“…b) polystyrene beads freely float in DI water, were propelled towards the focal plane by vortex beam created by AL28 . Motion of the particles is capture with high speed imaging system coupled to the optics of the inverted microscope.…”
mentioning
confidence: 99%